Pengaruh Likuiditas, Ukuran Perusahaan, dan Solvabilitas Terhadap Profitabilitas Perusahaan - Aan Noviana; Nursiam Nursiam (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine and analyze the effect of liquidity, firm size, and solvability on corporate profitability in manufacturing companies in the retail sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. This study employs a quantitative approach using secondary data in the form of annual financial statements obtained from the official IDX website (www.idx.co.id) and the respective companies' websites, analyzed using multiple linear regression with SPSS version 26. The population used in this study consists of all manufacturing companies in the retail sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling technique used was purposive sampling based on specific criteria, resulting in 46 companies or 135 data units over four years. After removing 5 outlier data points, the final sample consisted of 130 observations. The findings indicate that: (1) Liquidity (CR) has no significant effect on corporate profitability; (2) Firm size (SIZE) has no significant effect on corporate profitability; (3) Solvability (DAR) has a significant effect on corporate profitability. The Adjusted R² value of 0.043, or 4.3%, indicates that the profitability variable can be explained by the independent variables by 4.3%, while the remaining 95.7% is explained by other variables outside the research model.